GENDER CONSTRUCTION IN SPORTS, FAMILY HABITUS AND “GENDER REGIME” - Christine Mennesson; Lucie Forté (Society Register)
This article is based on data collected during a qualitative survey on children's leisure practices and family socialisation patterns. The paper focuses more specifically on the cross effects of gender and social class on the construction of body hexis and relationship to sports. The results show that several dimensions of family habitus must be taken into account: lifestyles, way in which parents divide the tasks of raising children and relationship they have with social competition or gender norms. Moreover, taking these different dimensions into account must be accompanied by an analysis of the concrete modes of socialization within the family and the practice context.